Bone marrow sinusoidal endothelium controls terminal erythroid differentiation and reticulocyte maturation - Heil, Joschka; Olsavszky, Victor; Busch, Katrin; Klapproth, Kay; Torre, Carolina de la; Sticht, Carsten; Sandorski, Kajetan; Hoffmann, Johannes; Schönhaber, Hiltrud; Zierow, Johanna; Winkler, Manuel; Schmid, Christian David; et al. (Nature Communications, 2021)
Within the bone marrow microenvironment, endothelial cells (EC) exert important functions. Arterial EC support hematopoiesis while H-type capillaries induce bone formation. Here, we show that BM sinusoidal EC (BM-SEC) actively control erythropoiesis. Mice with stabilized β-catenin in BM-SEC (Ctnnb1OE-SEC) generated by using a BM-SEC-restricted Cre mouse line (Stab2-iCreF3) develop fatal anemia. While activation of Wnt-signaling in BM-SEC causes an increase in erythroblast subsets (PII-PIV), mature erythroid cells (PV) are reduced indicating impairment of terminal erythroid differentiation/reticulocyte maturation. Transplantation of Ctnnb1OE-SEC hematopoietic stem cells into wildtype recipients confirms lethal anemia to be caused by cell-extrinsic, endothelial-mediated effects. Ctnnb1OE-SEC BM-SEC reveal aberrant sinusoidal differentiation with altered EC gene expression and perisinusoidal ECM deposition and angiocrine dysregulation with de novo endothelial expression of FGF23 and DKK2, elevated in anemia and involved in vascular stabilization, respectively. Our study demonstrates that BM-SEC play an important role in the bone marrow microenvironment in health and disease.
Gesehen am 20.12.2021